Heat and Mass Transfer in Conjugate Food Freezing/Air Natural Convection - Lemus-Mondaca, R (2012)
This work reports a study of the heat and mass transfer during the freezing of a block of beef in the freezer compartment of a household refrigerator. It takes into account the natural convection in air coupled to the heat conduction and water diffusion in the meat. The nonlinear partial differential equations describing mass conservation, linear momentum, energy and species concentration in two dimensions are solved with the SIMPLE algorithm and the finite volumes method. The results obtained include the unsteady state description of air movement as well as temperature and water concentration in the air, and temperature and water concentration distribution in the meat. The predicted weight loss of the food reaches a value of 1.5%. © 2012 Elsevier Ltd and IIR. All rights reserved.